2020
DOI: 10.3390/ani10101739
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Investigations and Tissue Bioaccumulation of Heavy Metals in Grey Mullet from the Black Sea (Bulgaria) and the Ionian Sea (Italy)

Abstract: The environmental monitoring of chemical toxicants has been a widely studied topic in the last few decades. The main aim of the present study was to determine the total concentration of nine elements (Cd, Cr, Pb, Ni, Al, Cu, Fe, Mn, and Zn) in the fish species grey mullet (M. cephalus) and in the coastal marine waters collected from various sampling points along the Black Sea (Bulgaria) and the Ionian Sea (Italy). Further, those results were applied to predict the pollution degree in those coastal marine envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 52 publications
0
20
1
Order By: Relevance
“…Many studies have been conducted on the concentrations of PTMs in fish in many regions or countries, such as the Red Sea [19][20][21], India [22][23][24], Pakistan [14,[25][26][27][28], Indonesia [29,30], Persian Gulf or Iran [31][32][33][34][35], Bangladesh [36][37][38], Tanzania [39], Turkey [40], China [41][42][43], Mediterranean Sea [44,45], Aegean Seas of Turkey [46,47], Mexico [48], the Black Sea (Bulgaria), and the Ionian Sea (Italy) [49].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on the concentrations of PTMs in fish in many regions or countries, such as the Red Sea [19][20][21], India [22][23][24], Pakistan [14,[25][26][27][28], Indonesia [29,30], Persian Gulf or Iran [31][32][33][34][35], Bangladesh [36][37][38], Tanzania [39], Turkey [40], China [41][42][43], Mediterranean Sea [44,45], Aegean Seas of Turkey [46,47], Mexico [48], the Black Sea (Bulgaria), and the Ionian Sea (Italy) [49].…”
Section: Introductionmentioning
confidence: 99%
“…These new diagnostic methods have brought great benefits to the veterinary medicine and to the study of fish haematology. Previous studies on various fish species, have shown a marked variation in haematological and hematochemical parameters due to exposure to various pollutants [13,184,190,198,199]. Among the various polluting substances and materials, MPs represent the most plentiful pollutants on Earth [200] due to their ubiquitous presence within the aquatic environment [201].…”
Section: Impact Of Micro and Nano Plastics Bioaccumulation On Blood Response In Fishmentioning
confidence: 99%
“…where R is the ratio of 15 N/ 14 N or 13 C/ 12 C, and the background materials of δ 15 N and δ 13 C are N 2 in the atmosphere and carbon in Vienna Pee Dee Belemnite (VPDB). The precision of the analytical technique was <0.20‰ for δ 13 C and <0.30‰ for δ 15 N.…”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…Chowdhury et al [9] found in adult rainbow trout that dietary Cd resulted in a 26-fold increase in plasma Cd level over 45 days. Despite low concentrations of trace metals in water and sediment, the characteristics of bioaccumulation in organism tissue can be transferred to fish tissue (muscle, gills, liver, stomach, and intestine), they may ultimately accumulate to dangerous levels and pose a potential risk to human health [10][11][12].…”
Section: Introductionmentioning
confidence: 99%